Earth in upheaval - Velikovsky, Immanuel (Pocket Books, 1955)
Citing evidence from the natural sciences the author reveals global catastrophes in prehistorical times that altered the climate and geography of the earth. The astounding theory of extra-terrestrial forces that radically reconstructs the earth's history.